ANTIFUNGAL POTENTIAL OF A BRASSICACEOUS WEED Sisymbrium irio AGAINST Macrophomina phaseolina - JAVAID,A. (2017)
ABSTRACT Macrophomina phaseolina, a soil-borne plant pathogen, has the ability to cause diseases in about 500 plant species. Unfortunately, so far no registered fungicide is available against this fungal pathogen. In the present study, different extracts of Sisymbrium irio, a weed of family Brassicaceae, were tested for evaluation of their antifungal activity against M. phaseolina. In screening bioassays, antifungal activity of methanolic extracts of 1% to 6% concentrations of different parts (leaf, stem, root and fruit) of the weed was assessed against the fungal pathogen. Methanolic leaf and root extracts significantly reduced fungal biomass up to 59% and 69% over control, respectively. Methanolic leaf and root extracts were further partitioned using four organic solvents namely n-hexane, chloroform, ethyl acetate and n-butanol in order of increasing polarity. Antifungal activity of different concentrations of these fractions (3.125, 6.25, …, 200 mg mL-1) was assessed against the pathogen. Chloroform and n-hexane fractions of methanolic leaf extract showed highly pronounced activity resulting in 35-75% and 15-87% reduction in fungal biomass over corresponding control treatments, respectively. Likewise, the highest concentration (200 mg mL-1) of chloroform, ethyl acetate and n-butanol fractions of methanolic root extract reduced fungal biomass by 75%, 70% and 87%, respectively. The present study concludes that chloroform and n-butanol fractions of methanolic leaf and root extracts of S. irio, respectively, contain potent antifungal constituents for management of M. phaseolina.